Injustice in Indonesia’s Legal Protection Framework for Outsourced Workers - Iswantoro Iswantoro; Tajudeen Sanni (Lembaga Contrarius Indonesia, 2025)
This study analyzes the regulatory weaknesses in the legal protection of outsourced workers in Indonesia, particularly in relation to the fulfillment of justice as mandated by Pancasila and the 1945 Constitution of the Republic of Indonesia. The enactment of Law Number 11 of 2020 on Job Creation has significantly altered the orientation of labor law, shifting it toward economic efficiency and investment facilitation. This shift has resulted in the erosion of normative labor protections and increased vulnerability of outsourced workers, manifested in job insecurity, unequal bargaining power, limited social security coverage, and insufficient welfare guarantees. The primary objective of this research is to evaluate the extent to which existing labor regulations fail to embody substantive justice and to formulate a normative framework for reconstructing labor law in accordance with constitutional values. This study employs an empirical juridical research method with a socio-legal approach, integrating doctrinal legal analysis with empirical data to assess the interaction between legal norms and labor practices. The findings demonstrate that the current regulatory framework prioritizes labor market flexibility over worker protection, leading to structural injustice and normative inconsistencies within the industrial relations system. The study concludes that a comprehensive reconstruction of labor law is necessary through reforms in legal structure, legal substance, and legal culture, grounded in the principles of social justice, humanity, and public welfare, in order to ensure substantive justice and constitutional compliance in the protection of outsourced workers in Indonesia.